H.264/advance video coding standard - Khalifa, Othman Omran; Issa, Sinzobakwira; Hassan Abdalla Hashim, Aisha (IIUM Press, 2011)
A remarkable development was achieved in the field of video compression in the past few decades. The first MPEG and H.264 generations were engines behind the triumph and marketability of digital video compression. The ITU-T and ISO/IEC are the main actors in developing image and video coding standard. These two bodies have emerged jointly in developing the newer standard H.264/AVC in the world of telecommunication particularly in the area of video compression. With the aim of doubling the compression effectiveness, the ITU-T video coding expert group proposed a new video coding standard which would overshadow the existing one [1]. The joint video team (JVT) was formed consisting of the members of ITU-T VCEG and the ISO/IEC moving picture experts group (MPEG) in 2001 to start the development of the resulting effort based on the expertise of the two factions